Review Of Stockpile Management To Reduce The Risk Of Coal Self-Heating, Which Can Cause Spontaneous Combustion - Edy Nursanto; Rahimatul Fadhilah; Nurkhamim (UIR PRESS, 2024)
One of the energy requirements for fuel is in the form of solid hydrocarbons and as basic materials or feedstocks. Coal is formed from deposits of organic plant compounds that grow in an oxygen-free environment and are influenced by temperature and pressure for a long time. Based on the coal formation process, coal from the highest to the lowest level is anthracite, bituminous, sub-bituminous, and lignite. Low-grade coal has a faster oxidation rate than high-grade coal because it contains inherent moisture, oxygen, and carbon in large quantities, has high porosity, and causes an increase in activation energy resulting in evaporation and a continuous increase in temperature causing spontaneous combustion. Monitoring and control of coal, especially in the stockpile area as a temporary storage place, is carried out to prevent oxidation and self-burning, namely by arranging the piling pattern and applying demolition principles by taking into account the length of the pile, forming the design of the stockpile base surface, calculating the volume, height, side slope, and distance between piles, as well as taking into account wind speed and direction, which greatly influence particle size, porosity, and the rise in temperature of the coal during self-heating. Efforts to handle self-heating in coal can be made by creating drainage in the stockpile area, reducing the height, and forming a slope angle of 15–30° to facilitate compaction of the coal pile so that it can be stored for a long time, as well as minimizing losses from spontaneous combustion and early self-heating detection for safe coal storage.